Rwanda : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
Exporters are permitted to sell their foreign export earnings freely in the exchange market or to retain them in accounts with domestic banks. The surrender requirements for export earnings of coffee and tea have been reduced from 90 percent to 50 percent at end-1996 and eliminated at end-December 1997. The remaining export restriction-a 16 percent ad valorem export tax on coffee that was introduced in April 1998 in place of a variable export tax-has been eliminated effective January 1, 1999.